The profound of students’ supervision practice in higher education to enhance student development - Ismail, Affero; Zainal Abiddin, Norhasni; Hassan, Razali; Ro’is, Ihsan (Canadian Center of Science and Education, 2014)
Supervision has become a highlight in higher education in recent years. While striving for the quality of education, the stress in research supervision has become dominant. Excellent research can contribute to the prominent of institutions’ image. This paper accumulates the models from expert scholars in students’ development regarding supervision issue. The models have their own functions and strengths. This can be proved by revising at the thorough implementation. Most supervision approaches and models have mutual aptitude: (1) The relationship establishment that was built on good communication, expectation and confidentiality; (2)The formulation of student-based, agreed upon aims and outputs; and (3)A systematic training and learning process in relation to the goals. This paper will discuss appropriate models that can be studied in student development.